Um ambiente para o auxílio à aprendizagem de habilidades laparoscópicas usando realidade aumentada e gamificação - Valério, Julian Rodrigues (2016)
Minimally Invasive Surgeries (MIS) require learning and training unconventional skills of surgeons (e.g., hand-eye coordination, manual dexterity). The teaching and learning processes usually involve the use of simulating box-trainers, which allow the training of such skills with navigation activities and simple coordination. In this paper, we propose to extend laparoscopic box-trainers with Augmented Reality (AR) and gamification techniques. The proposal uses an additional camera and object tracking to monitor the movement of handled objects. Our boxtrainer simulator is able to assess the performance of students during the training activity (e.g., time to complete the activity, errors). The main part of the simulator is the LARG framework, which is developed and used to implement the gamified activities. The framework integrates the OpenCV and Ogre3D libraries. It offers mechanisms that enable rendering of 3D images in activities, tracking of objects, detecting patterns and inserting gamified components. We designed and developed two activities for the training of navigation skills. A usability evaluation of the proposal was implemented with a group of eighteen members who performed two activities. Results indicate a good usability acceptance of the box-trainer. We also observed a significant difference in performance between surgeons and students of the first year of residency, thus indicating the simulator can be successfully used in learning MIS skills.